2018
DOI: 10.15537/smj.2018.3.21679
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hypocalcemia and its relation to vitamin D and calcium supplementation

Abstract: Objectives:To assess the prevalence of hypocalcemia in outpatient clinic neonates and its relation to vitamin D and calcium supplementation.Methods:This cross-sectional analytical study was conducted at the University Teaching Hospital from May to October 2016. Data were collected from 100 neonates by interviewing mothers using a structured questionnaire; which included socio-demographic information, maternal and neonatal history; in addition to investigations of serum calcium total and ionized and serum vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…In a prior analysis, we also found that gestational age was not associated with neonatal vitD deficiency (data not shown). These findings are in keeping with previous studies, which have reported conflicting results regarding gestational age [18,27,28] and maternal education [11,14] as potential risk factors of neonatal vitD deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…In a prior analysis, we also found that gestational age was not associated with neonatal vitD deficiency (data not shown). These findings are in keeping with previous studies, which have reported conflicting results regarding gestational age [18,27,28] and maternal education [11,14] as potential risk factors of neonatal vitD deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study 19 reported high incidence of hypocalcemia in neonatal seizures admitted in level III neonatal intensive care units. Recent studies by Elsary et al 20 and Do HJ et al 21 have reported neonatal hypocalcemia and neonatal seizures and support the findings of present study. The limitations of present study include; first-small sample size, second-poor ethnical group of sample population was selected, third-other variables were not measured due to financial issues.…”
Section: Discussionsupporting
confidence: 92%
“…This finding of ours is in contradictition to general findings in other studies done in the past. [3][4][5] However, study done by Elsary AY et al 11 also had larger proportion of term babies in comparison to preterm babies like ours. Since our hospital is a referral hospital, substantial number of babies with perinatal asphyxia and preterm babies who presented to our set up had already received prophylactic IV calcium.…”
Section: Discussionmentioning
confidence: 71%
“…This fact has been demonstrated in other studies too. 11,12 We had found mean serum calcium level of 8.6 mg/ dl for term babies and 8.1 mg/dl for preterm babies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation